1995
DOI: 10.1111/j.1365-2796.1995.tb01214.x
|View full text |Cite
|
Sign up to set email alerts
|

Euthyroid Graves' disease showing no thyroid abnormalities except positive thyroid‐stimulating antibody (TSAb): two case reports

Abstract: We report two cases of euthyroid Graves' disease in women who had ophthalmopathy without previous history of hyperthyroidism. Enlargement of extraocular muscles was observed by magnetic resonance imaging (MRI). The patients had no thyroid enlargement and their serum concentrations of free T4, free T3, and TSH were normal. The sera were negative for antithyroid microsomal and thyrogobulin antibodies, and anti-TSH receptor antibodies measured by radioreceptor assay. T3 suppression test results were normal. Only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Watanabe et al reported the relationship between TSAb activity and severity of ophthalmopathy [19]. In our case, the titers of both TSAb and TRAb decreased slightly and transiently during methylprednisolone therapy; these changes correlated with ocular manifestations.…”
Section: Discussionmentioning
confidence: 52%
“…Watanabe et al reported the relationship between TSAb activity and severity of ophthalmopathy [19]. In our case, the titers of both TSAb and TRAb decreased slightly and transiently during methylprednisolone therapy; these changes correlated with ocular manifestations.…”
Section: Discussionmentioning
confidence: 52%
“…Thyroid-stimulating immunoglobulin (TSI) measurement has been reported to be a useful and possibly more sensitive marker of euthyroid GO than TBII measurement in Asians 2 21 22. This is also the case for primarily hyperthyroid patients 23.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Because most cases involving euthyroid TAO showed no thyroid abnormalities except testing positive for thyroidstimulating hormone receptor antibodies (TRAbs), 7,9 the clinical significance of TRAb as a criterion in the diagnosis of euthyroid TAO has been suggested. 3,6 Recently, Eckstein et al 10 reported that the TRAb titer was low in euthryoid and hypothyroid patients, suggesting that a more sensitive assay technique was necessary to utilize the TRAb assay for diagnosis of euthyroid/hypothyroid TAO.…”
Section: Introductionmentioning
confidence: 99%